The Influence Of Organizational Commitment And Work Motivation On The Performance Of Employees At Prasetya Bunda Tasikmalaya Hospital - Aziz, Apriyand Muharam Abdul; Rahwana, Kusuma Agdhi; Risana, Dudu (Journal of Management, Economic, and Accounting, 2024)
The purpose of this research is to find out and analyze the influence of organizational commitment and work motivation partially and simultaneously on the performance of Prasetya Bunda Hospital employees in Tasikmalaya. The population that will be the subject of the research is the employees of the Medical Department of the Prasetya Bunda Hospital in Tasikmalaya with a sample of 190 employees. The research method used is quantitative, with data collection using questionnaires, interviews, field studies, and literature studies. Data analysis is done with Validity Test, Reability, Interval Value (NJI), Method Of Successive Interval, Classic Assumption Test and multiple linear regression test to test the relationship between variables of organizational commitment, work motivation, and employee performance. The important points from the results of the research are the commitment of the employees of Prasetya Bunda Hospital Tasikmalaya which is included in the high category. The work motivation of Prasetya Bunda Tasikmalaya Hospital employees is included in the very high category. The performance of Prasetya Bunda Tasikmalaya Hospital employees is included in the very high category. Simultaneous Effects: Organizational commitment and work motivation simultaneously have a significant effect on Employee Performance on the employees of Prasetya Bunda Hospital Tasikmalaya. Partial Effect: Partially, Organizational Commitment has a significant effect on Employee Performance in Prasetya Bunda Tasikmalaya Hospital employees, as well as work motivation. With this result, it can be concluded that organizational commitment and work motivation play an important role in encouraging high employee performance in the employees of Prasetya Bunda Hospital Tasikmalaya.